Regional general equilibrium modelling with forward-looking agents: An application to the 2014-2020 European structural regional investments - Francesca Crucitti; Patrizio Lecca; Philippe Monfort; Simone Salotti (European Commission, Joint Research Centre (JRC), 2022)
We investigate the effects of the 2014-20 European structural funds with a general equilibrium model calibrated on the NUTS 1 regions of the EU. We assume forward-looking agents to account for expectations and long-lasting effects of the policy. The almost exteuro260 billion of investments lead the European GDP to be 0.3% higher in 2022 than it would be in the absence of the policy. Interestingly, this effect is lower than what a model with myopic agents would suggest. The regional distribution of the differences in the GDP impacts between the two settings indicates that the largest deviations are recorded for the net recipient regions, with interesting implications regarding the policy credibility, the nature of the interventions and their duration.
Keywords: C68; D58; R13; 330; general equilibrium modelling; forward-looking behaviour; regional economics; cohesion policy